Impact of alcohol consumption, substance use, and smoking on treatment outcomes in tuberculosis: a systematic review and meta-analysis - Bahram Heshmati; Sanaz Omidi; Younes Mohammadi (Systematic Reviews)
Abstract Background This study aimed to elucidate the influence of alcohol, smoking, and substance use on tuberculosis (TB) treatment failure using a meta-analysis approach. Method A comprehensive search strategy was developed and applied to three major databases: MEDLINE, Web of Science, and Scopus. Additionally, Google Scholar, and Google were used to locate grey literature. Studies were identified through title and abstract screening, followed by a full-text review for eligibility. The Newcastle–Ottawa Scale checklist was employed to assess the quality of included studies. Pooled odds ratios (OR) with 95% confidence intervals (CI) were calculated for each factor. Results The initial database search and other sources yielded 10,518 articles. After applying inclusion criteria, 19 studies with a total of 180,119 participants were selected for the meta-analysis. The results revealed significant associations between all three factors and treatment failure. Pooled ORs indicated that alcohol consumption (OR 2.05; 95% CI 1.65 to 2.55), smoking (OR = 1.85; 95% CI 1.44 to 2.37), and substance use (OR 2.04; 95% CI 1.63 to 2.55) were each associated with an increased risk of TB treatment failure. Additionally, the majority of included studies demonstrated high methodological quality. Conclusion Our findings suggest that alcohol, smoking, and substance use are significant risk factors for unsuccessful TB treatment. To enhance TB treatment efficacy, preventive interventions aimed at reducing these behaviors before treatment initiation are recommended.